2011
DOI: 10.1111/j.1551-2916.2011.04507.x
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Barium Strontium Titanate Ceramics Prepared by Spark Plasma Sintering

Abstract: Transparent ferroelectric ceramics are valuable for many applications in electro‐optical devices. In this paper, transparent barium strontium titanate (BST) ceramics were prepared by spark plasma sintering and thermal treatment. The microstructures and optical properties of the transparent BST samples were investigated. The densities of the BST samples were nearly theoretical and the samples were optically transparent. Both the transmittances at 633 nm of the Ba0.3Sr0.7TiO3 and Ba0.4Sr0.6TiO3 ceramics with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Hence the ac conductivity is dominant one. The ac conductivity is obtained from the formula σ ac = ε ε 0 ω tan δ ----------- (7) where ω is the angular frequency and ε 0 is the dielectric constant in free space. The ac conductivity at different temperatures is studied by measuring the dielectric constant and the loss tangent at those temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence the ac conductivity is dominant one. The ac conductivity is obtained from the formula σ ac = ε ε 0 ω tan δ ----------- (7) where ω is the angular frequency and ε 0 is the dielectric constant in free space. The ac conductivity at different temperatures is studied by measuring the dielectric constant and the loss tangent at those temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, BST compounds are now being investigated with regard to various electronic applications. It has been found that BST has applications in piezoelectric sensors, dynamic random access memories (DRAM), microwave phase shifters, tunable filters and uncooled infrared detectors for its high dielectric, ferroelectric, and pyroelectric properties [6][7][8]. Since all these properties are strongly related to the microstructure of the ceramics, the homogeneity of the materials is important Traditionally, BSTs are prepared by the ceramic method, in which the carbonates of barium, strontium, and titanium oxide are calcined at high temperature (1200 o C) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…5 Spark plasma sintering (SPS) is one of the most promising processes to attain this goal at relatively lower temperatures over a short time period. 10,11 In this work, we report that fully dense Ba 0.65 Sr 0.35 TiO 3 (BST) ceramics with a Curie temperature around room temperature were prepared successfully by SPS and that significantly enhanced dielectric strength and EC effect were obtained. The dielectric strength was further enhanced by introducing a small amount of manganese into the BST sample, and subsequently the ECE was greatly improved in the present ceramics.…”
Section: Introductionmentioning
confidence: 92%
“…proposed high EC temperature changes could be achieved in bulk materials by enhancing their dielectric strengths through better process to prepare a flaw‐free sample with full density . Spark plasma sintering (SPS) is one of the most promising processes to attain this goal at relatively lower temperatures over a short time period …”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, spark plasma sintering, which allows for quick densification has been found to be a useful and efficient method in tailoring the microstructure of ceramics [19][20][21]. The advantages of SPS method, such as low sintering temperature, short sintering time and microscopic electrical discharges between particles, make it suitable to control the grain size and grain boundary of ceramics and to tailor the configuration and interface of composites [22][23][24].…”
Section: Introductionmentioning
confidence: 99%